Avaliação da distorção harmônica em um transformador de 300 kVA da Universidade Federal Tecnológica Federal do Paraná, campus Curitiba, sede Centro - Galindo, Martins Dario Gonçalves (2016)
This paper shows a field research using a class A power analyzer to get data from current and voltage harmonic distortion in an electrical installation supplied by a 300 kVA transformer and compare them with the IEEE std 519-2014, the PRODIST 8 module and the IEC 61000-3-6 recommendations. It is observed what the transformer capability to provide load without overheating due to harmonic currents, following the IEEE Std C57.110-1998 recommendations. Approaches to the mathematical concepts of harmonics, the main causes of this phenomenon, mitigation methods and a case study on an electrical installation with similar characteristics to the UTFPR. Sizing of a shunt passive filter to trap the 3rd harmonic current is developed, computational simulation is used to get the current and voltage harmonic distortion after the filter application and what is the new transformer capability to provide power to the load without overheating.